In situ stress field evaluation of deep marine tight sandstone oil reservoir: A case study of Silurian strata in northern Tazhong area, Tarim Basin, NW China. (February 2017) - Yin, Shuai; Ding, Wenlong; Zhou, Wen; Shan, Yuming; Xie, Runcheng; Guo, Chunhua; Cao, Xiangyu; Wang, Ruyue; Wang, Xinghua
Abstract: Deep marine tight sandstone oil reservoirs are the subject of considerable research around the world. This type of reservoir is difficult to develop due to its low porosity, low permeability, strong heterogeneity and anisotropy. A marine tight sandstone oil reservoir is present in the Silurian strata in the northern Tazhong area of the Tarim Basin, NW China, at a depth of more than 5000 m. The porosity is between 6% and 8%, and the gas permeability is between 0.1 and 1 × 10 −3  μm 2 . The features of this type of reservoir include the poor effects of conventional fracturing modifications and horizontal wells, which can lead to stable and low levels of production after staged fracturing. Here, we conduct a comprehensive evaluation of the mechanical properties of the rock and the in situ stress of the target tight sandstones by using numerous mechanical and acoustic property tests, conducing crustal stress analysis and using data from thin section observations. The dispersion correction technique is used to transform velocity at the experimental high frequency (1 MHz) to velocity at the logging frequency (20 kHz). The logging interpretation models of the transverse wave offset time, mechanical parameters and in situ stress are calculated, and each model represents a high precision prediction. Simulating the in situ stress field of the Silurian strata using a three-dimensional finite element method demonstrates that the average error between the simulation result and the measured value is less than 6%. The planar distribution of each principal stress is mainly controlled by the burial depth and fault distribution. By conducting in situ stress orientation analysis for the target layer via the analysis of paleomagnetism, borehole enlargement, fast shear wave orientation and stress field simulation, we show that the direction of the maximum horizontal stress is N45E. In this paper, a typical and successful comprehensive evaluation of the stress field of the deep tight sandstone oil reservoir is provided. Highlights: A set of logging evaluation method of geomechanical parameters has been established. A new model has been established to predict the rock triaxial compressive strengths. The conversion relationships between the rock dynamic and static elastic parameters have been established. The logging evaluation method of rock in situ stresses has been established. 3D models of the in situ stress fields have been developed. The planar distribution of stresses is controlled by the burial depth and fault distribution.